The Relationship Between Psychological Support And Religious Values Among The Adolescents In The Preparatory Year At The Muslim University In Al-Madīnah Al-Munawwarah (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study aimed at investigating the relationship between psychological support and religious values among the adolescents in the preparatory year at the Muslim University in Al-Madīnah Al-Munawwarah. The study employed the descriptive analytical method, and the researcher developed the study instruments that consisted of two scales; the psychological support scale, which consisted of (41) items distributed to four domains: (emotional support, morale cognitive support, recognition and status support, as well as social support); and the religious values scale which consisted of (53) items distributed to three domains: (ideological values, worship values, as well as moral values). The validity and reliability of study instruments were verified. The study sample consisted of (192) preparatory-year students studying at the Muslim University in Al-Madīnah Al-Munawwarah. The results showed that the level of psychological support, with its domains, was of a high degree, with a mean that ranged between (3.75 - 4.06), and it was ranked as follows; (cognitive morale support , recognition and status support, social support, and emotional support). The mean of psychological support in total was (3.91) . The level of religious values was also of a high degree, with a mean that ranged between (3.64 - 4.44), in the following order (ideological values, worship values, and finally moral values), and the mean of the religious values in total was (3.92). The results showed that there is a statistically significant positive relationship between the psychological support and the religious values.